Lessons on scaling sustainable practices for resilient agrifood systems - Waswa, Boaz; Nzuki, Esther; Mwendia, Solomon; Ketema, Dessalegn; Nduah, Alex; Njeri, Linda; Waweru, Daisy (Bioversity International and International Center for Tropical Agriculture, 2025)
The workshop on Scaling Sustainable Practices for Resilient Agrifood Systems, held from November 16-18, 2025, in Tawa, Makueni County, brought together stakeholders from research, government, private sector, and farmer organizations to discuss strategies for improving resilience and sustainability in agrifood systems. The workshop was organized by the Scaling for Impact Science Program in collaboration with the Sustainable Farming, Multifunctional Landscape, and Gender Equity and Inclusion Science Programs of the CGIAR. It was built on work initiated under the Ukama Ustawi Initiative on conservation agriculture and system diversiﬁcation in Nakuru, Embu, and Makueni Counties. Bringing in partners to share experiences expanded learning among participants and organizations. Discussions highlighted integrated approaches combining technological, social, and financial innovations, alongside gender-transformative and market-led models. Key lessons emphasized context-specific solutions, participatory learning, digital advisory tools, and multi-stakeholder partnerships as critical enablers of scale.